Samih Al-Qasim's Poem Kama Nasya' as a Representation of Palestinian Social Reality: A Sociology of Literature Study - Ichsanul Hasri; Aiyub Berdan; Irwan Mus; Ivan Aulia Trisnady; Sumardi (Pusaka Cendekia Indonesia Foundation, 2025)
Palestinian poetry, particularly the works of Samih Al-Qasim, constitutes a form of artistic expression that cannot be separated from the socio-political realities surrounding it. As noted by Jayyusi (1992), Palestinian literature emerges from a collective historical experience marked by oppression, alienation, and the struggle to preserve identity. In this context, poetry functions not only as an aesthetic expression but also as a medium for articulating the social and political consciousness of the Palestinian people. Samih Al-Qasim, as one of the most significant Palestinian poets, consistently presents poems that reflect the relationship between the individual and the community. His works represent the tension between personal experience and the collective suffering endured by his people.This article aims to analyze the poem “Kama Nasya” by Samih Al-Qasim using the sociology of literature approach proposed by Lucien Goldmann (1964). This approach is chosen because it enables literary works to be read as expressions of the worldview of a collective subject, rather than merely as products of an individual poet’s creativity. The research employs a qualitative-descriptive method with interpretative analysis techniques focusing on the poetic structure, including diction, metaphor, and patterns of intersubjective relations. The structural analysis is then connected to the social and historical contexts that underlie the poem’s creation, as suggested in sociological studies of literature. Thus, this study seeks to systematically relate the structure of meaning in the text to the social conditions of Palestinian society. The results of the analysis indicate that the poem “Kama Nasya” not only expresses individual emotional experiences but also reflects the collective voice of the Palestinian people who have experienced marginalization and structural oppression. The relationship between the lyrical subjects “I” and “you” in the poem can be understood as a symbolic representation of the individual’s relationship with the community and the homeland. Through metaphorical language and reciprocal, egalitarian relations, the poem articulates values of solidarity, the resilience of identity, and the continuity of life’s meaning. Therefore, as emphasized by Said (1979), poetry functions as an important medium for social and cultural critique in the context of colonialism, while simultaneously serving as a means of symbolic resistance against domination and the erasure of collective identity. Puisi Palestina, khususnya karya-karya Samih Al-Qasim, merupakan bentuk ekspresi artistik yang tidak dapat dilepaskan dari realitas sosial-politik yang melingkupinya. Sebagaimana dikemukakan Jayyusi (1992), sastra Palestina lahir dari pengalaman historis kolektif yang ditandai oleh penindasan, keterasingan, dan perjuangan mempertahankan identitas. Dalam konteks ini, puisi tidak hanya berfungsi sebagai ungkapan estetis, tetapi juga sebagai medium artikulasi kesadaran sosial dan politik masyarakat Palestina. Samih Al-Qasim, sebagai salah satu penyair penting Palestina, secara konsisten menghadirkan puisi-puisi yang merefleksikan relasi antara individu dan komunitasnya. Karya-karyanya merepresentasikan ketegangan antara pengalaman personal dan penderitaan kolektif yang dialami oleh bangsanya. Artikel ini bertujuan untuk menganalisis puisi “Kama Nasya” karya Samih Al-Qasim dengan menggunakan pendekatan sosiologi sastra yang dikemukakan oleh Lucien Goldmann (1964). Pendekatan ini dipilih karena memungkinkan pembacaan karya sastra sebagai ekspresi pandangan dunia suatu subjek kolektif, bukan sekadar hasil kreativitas individual penyair. Metode penelitian yang digunakan adalah kualitatif-deskriptif dengan teknik analisis interpretatif terhadap struktur puisi, meliputi diksi, metafora, dan pola relasi antarsubjek. Analisis struktural tersebut kemudian dihubungkan dengan konteks sosial dan historis yang melatarbelakangi lahirnya puisi, sebagaimana disarankan dalam kajian sosiologi sastra. Dengan demikian, penelitian ini berupaya mengaitkan struktur makna teks dengan kondisi sosial masyarakat Palestina secara sistematis. Hasil analisis menunjukkan bahwa puisi “Kama Nasya” tidak hanya mengekspresikan pengalaman emosional individu, tetapi juga mencerminkan suara kolektif masyarakat Palestina yang mengalami peminggiran dan penindasan struktural. Relasi antara subjek “aku” dan “engkau” dalam puisi dapat dipahami sebagai representasi simbolik dari hubungan individu dengan komunitas dan tanah airnya. Melalui bahasa metaforis dan relasi timbal balik yang setara, puisi ini menyuarakan nilai solidaritas, keteguhan identitas, dan keberlanjutan makna hidup. Oleh karena itu, sebagaimana ditegaskan oleh Said (1979), puisi berfungsi sebagai medium penting untuk kritik sosial dan kultural dalam konteks kolonialisme, sekaligus menjadi sarana perlawanan simbolik terhadap dominasi dan penghapusan identitas kolektif.